2002
DOI: 10.1103/physrevc.66.055208
|View full text |Cite
|
Sign up to set email alerts
|

η,ηphotoproduction and electroproduction off nucleons

Abstract: The photoproduction and electroproduction of the ,Ј mesons on nucleons are investigated within a relativistic chiral unitary approach based on coupled channels. The s-wave potentials for electroproduction and meson-baryon scattering are derived from a chiral effective Lagrangian, which includes Ј as an explicit degree of freedom and incorporates important features of the underlying QCD Lagrangian such as the axial U͑1͒ anomaly. The effective potentials are iterated in a Bethe-Salpeter equation and the cross se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 45 publications
1
79
1
Order By: Relevance
“…As we see, the WT term depends only on one parameter -the pion decay constant f , which is well known experimentally, f π = 92.4 MeV. However in UχPT calculations this parameter is usually taken to be larger than the experimental value, ranging from f = 1.15 f π to f = 1.36 f π [7][8][9][10][11][12][13][14][15][16][18][19][20][21], meaning to be a sort of average over the decay constants of the mesons involved in the various coupled channels. We will leave it as a free parameter of our fits.…”
Section: Chiral Unitary Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…As we see, the WT term depends only on one parameter -the pion decay constant f , which is well known experimentally, f π = 92.4 MeV. However in UχPT calculations this parameter is usually taken to be larger than the experimental value, ranging from f = 1.15 f π to f = 1.36 f π [7][8][9][10][11][12][13][14][15][16][18][19][20][21], meaning to be a sort of average over the decay constants of the mesons involved in the various coupled channels. We will leave it as a free parameter of our fits.…”
Section: Chiral Unitary Approachmentioning
confidence: 99%
“…From the studies of the meson-baryon interaction in s-wave approximation [8][9][10][11][12][13][14][15][16][18][19][20][21], it can be concluded that the significant term that allows one to get a good agreement with the experimental data is the Weinberg-Tomozawa (WT) one, which is of order O(p 2 ), and the addition of other terms such as the direct and crossed Born terms (O(p 2 )) as well as the NLO terms (O(p 4 )) only play a finetuning role. The corresponding diagrams are represented in figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The effective methods that are used to describe the dynamics of meson production reactions, include explicitly the baryon resonance states whose properties are extracted by comparing the predictions of the theory with the experimental data [9][10][11][13][14][15][16][17]. However, for a reliable realization of this goal, a model is required that can analyze different reactions over the entire energy range using a single Lagrangian density, which generates all non-resonance contributions from Born, u-and t-channel contributions without introducing new parameters.…”
Section: Meson Production In Photon-nucleon Reactionsmentioning
confidence: 99%
“…Moreover, because of an anomalous gluon component, the structure function of the η ′ meson is different from the one for mesons which are built up from quark-antiquark configurations. In a meson exchange model the intrinsic structure of the η ′ meson enters effectively through the form factors at the ρη ′ γ and ωη ′ γ vertices, which do not necessarily have to be of the standard monopole or dipole type [40][41][42][43][44]. In principle, the form factor at large |t| is given by the meson structure function at short distances and in case of η ′ meson might be defined through its gluon component.…”
Section: Vector Meson Exchange As Production Mechanismmentioning
confidence: 99%
“…Currently experimental and theoretical [40][41][42][43][44][45] studies of the reaction γp→η ′ p are motivated by the possibility to investigate excited baryons coupled to the η ′ meson. Assuming that the resonance production is the dominant contribution, an isobar analysis [37] of the SAPHIR data shows that the η ′ -photoproduction at photon energies 0.9≤E γ ≤2.6 GeV can be described by the coherent excitation of two resonances, S 11 (1897) and P 11 (1986).…”
Section: Introductionmentioning
confidence: 99%